OPTIMALISASI PEMANFAATAN FITUR PENJUALAN PADA ACCURATE ONLINE DALAM PENGEMBANGAN KOMPETENSI MUSYAWARAH GURU MATA PELAJARAN (MGMP) AKUNTANSI KABUPATEN KUDUS - Ashsifa, Izza; Mulyanto, Mulyanto; Handayani, Retno Tri; Whetyningtyas, Aprilia (Universitas YPPI Rembang, 2025)
The development of information technology has brought significant changes in various sectors, including the world of education. The Accounting Subject Teacher Conference (MGMP) in Kudus Regency plays a key role in ensuring the quality of teaching and learning in the field of accounting. In an effort to face the challenges of the times, the use of technology needs to be the main focus to increase the efficiency and effectiveness of the learning process. This community service aims to optimize the use of sales features in the Accurate Online platform as a technological solution that can support the development of MGMP Accounting competencies. By providing intensive training and mentoring, it is hoped that teachers can integrate this technology into their curriculum, increase the efficiency of the sales process, and overall improve the quality of accounting learning. It is hoped that this increase in competency will have a significant positive impact on the development of accounting education in Kudus Regency. The output of this community service program is increasing teacher competency, understanding technology, training modules, and publication of scientific articles in the Accredited National Service Journal.